Using PAMPs and DAMPs as adjuvants in cancer vaccines. Issue 12 (2nd December 2021) - Sun, Huanyou; Hu, Wenwen; Yan, Yinan; Zhang, Zichun; Chen, Yuxin; Yao, Xuefan; Teng, Ling; Wang, Xinyuan; Chai, Dafei; Zheng, Junnian; Wang, Gang
ABSTRACT: Immunotherapy for cancer has attracted considerable attention. As one of the immunotherapeutics, tumor vaccines exert great potential for cancer immunotherapy. The most important components in tumor vaccines are antigens and adjuvants, which determine the therapeutic safety and efficacy, respectively. After decades of research, many types of adjuvants have been developed. Although these adjuvants can induce strong and long-lasting immune responses in tumor immunity, they also cause more severe toxic side effects and are therefore not suitable for use in humans. With the development of innate immunity research, pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) are receiving more attention in vaccine design. However, whether they have the potential to become new adjuvants remains to be elucidated. The purpose of this review is to provide newideas for the research and development of new adjuvants by discussing the mechanisms and related functions of PAMPs and DAMPs.